PREVALENCE OF INTRINSIC RISK FACTORS FOR PATIENTS IN FALL OUTCOMES IN A SURGICAL CLINIC - Cristiane Ferraz da Silva; Suelen Reiniack; Bruna de Melo Souza; Karinne Cristinne da Silva Cunha (Universidade Federal do Paraná, 2016)
This study aimed to identify the prevalence of intrinsic fall risk factors during a patient's hospitalization. It also involved a search for records of patients' falls in January 2015 in a surgical hospitalization unit. Research was conducted from January to March 2015. Presence and absence of risk factors intrinsic to falling were considered. Five cases (5.1%) of falling were registered in 98 participants. Association of risk factors in patients that had fallen showed that 100% (5) of patients had risk factor of impaired vision, 80% (4) were more than 65 years old and had anemia. The principal focus was to reduce fall occurrences in the setting of this study. Future research intends to delve deeper on the subject of educational technology development in order to reduce the incidence of falling in the studied setting.